Beyond risk of amyloid and tau: Genetics of resilience using GWAS, imaging biomarkers, and longitudinal cognitive data. (1st February 2022) - Ramanan, Vijay K; Lesnick, Timothy G.; Przybelski, Scott A.; Heckman, Michael G.; Knopman, David S.; Radford, Jonathan Graff; Lowe, Val J; Mielke, Michelle M.; Jack, Clifford R.; Petersen, Ronald C.; Ross, Owen A.; Vemuri, Prashanthi
Abstract: Background: Large consortium case‐control studies have identified genetic risk variants for clinically‐diagnosed Alzheimer's dementia. However, a considerable fraction of older individuals display abnormal brain amyloidosis, an early biomarker of AD, in the absence of overt cognitive impairment, indicating that AD pathophysiology and its underlying genetic architecture represents only part of the picture when attempting to forecast clinical outcomes and target therapeutics. We hypothesized that novel genetic factors would be associated with differential cognitive resilience to (coping with) amyloidosis. Methods: We analyzed data for 546 amyloid‐PET positive older adults from the population‐based Mayo Clinic Study of Aging. Each individual's cognitive trajectory over time was modeled using a normalized composite score of memory performance assessed longitudinally. A genome‐wide association study was performed, testing >6 million genotyped and imputed variants for association with cognitive trajectory in the setting of amyloidosis. Data from 545 amyloid‐PET positive ADNI participants was used for replication. H‐MAGMA was utilized for gene‐ and pathway‐based analyses. Results: In the discovery sample (53% men, mean age 77 years), APOE ɛ4 was associated with worse memory trajectories as expected, and was thus covaried in the genome‐wide analyses. We uncovered a novel genome‐wide significant association with cognitive resilience at the MTMR7/CNOT7/ZDHHC2/VPS37A locus, and demonstrated replication in an independent cohort. Post‐hoc analyses confirmed this association as specific to the setting of elevated amyloid burden and not explained by differences in tau deposition or cerebrovascular disease. Additional significant associations were identified in HIVEP3, ADARB2, and pathways related to immune system activation. No convincing associations with resilience were identified for the bulk of known non‐ APOE AD case‐control risk variants. Conclusions: Through a novel design leveraging population‐based multimodal data, we discovered an association with cognitive resilience to amyloidosis for a locus on chromosome 8 which was specific to the amyloid‐positive setting, was independent of APOE ɛ4 or ɛ2, and displayed replication in an independent cohort. Functional data suggests that the causative variant at this locus may tag CNOT7, a gene linked to synaptic plasticity and hippocampal‐dependent learning and memory. Our data support the hypothesis that genetic heterogeneity is one of the factors that explains differential cognitive resilience to brain amyloidosis.